Career manual - Abdul Rahman, Shukran (IIUM Press, 2006)
This manual is written as a guide for students who are looking ~ for proper skills to obtain employment. It also serves as an important reference for students to know more about his or her personality and how it matches job demands. Of late, among the enigma faced by graduates and employers (both the government and corporate sectors) is the employability of fresh graduates when they step out into the world of unemployment. Efforts have been made to help graduates searching of employment appointment with a considerable allocation from the government to retool graduates with the necessary skill and knowledge. On a positive note, reports came to advise us that about 50 percent of those who enrolled in skills upgrading programs have been employed. However, it appears that providing such programs is not the only solution to the problem of graduates being unemployed. The fact that many graduates are not in the know of what they can do and what jobs suit them must be acknowledged. It is believed that if one is aware of his strengths and opportunities, knows how to seek appointment and has proper skills in job-seeking strategy, then the probability of being employed would be much higher. Thus, the objective of this book is to guide graduates to be aware of their personality, leading them to reach person-job-fit by outlining the suitable environment that matches their characteristics.